Medium-chain triglycerides (8:0 and 10:0) increase muscle mass and function in frail older adults: a combined data analysis of clinical trials - Ezaki, Osamu; Abe, Sakiko (Frontiers in Nutrition, 2023)
Background: Three clinical trials have examined the chronic effects of medium-chain triglycerides (MCTs) on muscle mass and function in frail older adults (mean age 85 years old). However, significant increases in muscle mass and some muscle function relative to long-chain triglycerides (LCTs) have yet to be shown, possibly due to the small number of participants in each trial. Objective: We re-analyzed these previous clinical trials to clarify whether MCT supplementation can increase muscle mass and function. Analysis: After adding post hoc tests to the original report, we compared changes in measurement between the MCT and LCT groups in the first 2 trials and conducted a combined data analysis. Methods: In a combined data analysis, changes from baseline in measurements at the 3month intervention in the MCTs-and LCTs-containing groups were assessed by analysis of covariance adjusted for baseline values of each measurement, age, sex, BMI, allocation to trial, habitual intakes in energy, protein, leucine, octanoic acid, decanoic acid, and vitamin D during the baseline period. The Mann-Whitney U test was used to analyze data on right and left knee extension times. Results: MCT supplementation for 3 months increased muscle function relative to LCT supplementation with and without an L-leucine (1.2 g) and vitamin D (cholecalciferol, 20 µg)-enriched supplement. In a combined data analysis (n=29 in MCTs, n=27 in LCTs), relative to supplementation with 6 g LCTs/day, supplementation with 6 g MCTs/day at dinner for 3 months significantly increased body weight (adjusted mean change from baseline: MCTs 1.2 vs. LCTs 0.2 kg, P=0.023), right arm muscle area (MCTs 1.4 vs. LCTs -0.7 cm 2 , P=0.002), left calf circumference (P=0.015), right-hand grip strength (MCTs 1.6 vs. LCTs 0.3 kg, P=0.017), right knee extension time (P=0.021), left knee extension time (P=0.034), walking speed (P=0.002), and number of iterations in leg open and close test (P<0.001) and decreased right triceps skinfold thickness (P=0.016).In frail older adults, supplementation for 3 months with a low dose (6 g/day) of MCTs (C8:0 and C10:0) increased muscle mass and function. These findings indicate the potential for the practical use of MCTs in daily life in treating sarcopenia.